2017
DOI: 10.1021/acs.est.7b01854
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Oxygen-Containing Functional Groups in Activated Carbon Facilitate Microbial Reduction of Ferrihydrite

Abstract: Carbonaceous materials are commonly used in agronomic and environmental applications primarily as geosorbents, but their redox properties that may affect biogeochemical reactions are rarely documented. Herein, the role of activated carbon (AC) mediating microbial reduction of ferrihydrite is studied. Our batch experiment results show that AC facilitated the reduction of ferrihydrite by Shewanella oneidensis MR-1, but the pretreatment of AC with HNO further increased the rate of reduction. The redox-active oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
104
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 65 publications
(133 reference statements)
5
104
2
Order By: Relevance
“…Figure S12a further showed the surface oxygen-containing functional groups were significantly positively correlated to methane production rates with a p value of 0.001. It is noteworthy that CV and quantification of the redox property have been employed to analyze the redox properties of biochar, hydrochar, and AC in previous studies, 18,19,39 while our results showed that they were not necessarily correlated to the promotion of biological process. The surface functional groups analysis based on FTIR and XPS provided valuable information to understand the role of hydrochar in AD.…”
Section: Effects Of Sh On the Key Microbial Populations Ascontrasting
confidence: 52%
See 1 more Smart Citation
“…Figure S12a further showed the surface oxygen-containing functional groups were significantly positively correlated to methane production rates with a p value of 0.001. It is noteworthy that CV and quantification of the redox property have been employed to analyze the redox properties of biochar, hydrochar, and AC in previous studies, 18,19,39 while our results showed that they were not necessarily correlated to the promotion of biological process. The surface functional groups analysis based on FTIR and XPS provided valuable information to understand the role of hydrochar in AD.…”
Section: Effects Of Sh On the Key Microbial Populations Ascontrasting
confidence: 52%
“…The methods (e.g., HNO 3 and H 2 O 2 pretreatment) to modify the hydrochar to increase surface oxygen-containing functional groups could be explored in future studies to further enhance AD efficiency. 18,20,54 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: Effects Of Sh On the Key Microbial Populations Asmentioning
confidence: 99%
“… 2017 ), a property that differentiate them from other redox-active carbon rich materials such as humic substances (Wu et al . 2017 ). Nevertheless, the role of BC redox reactions for influencing N 2 O emissions has not been experimentally verified with pure cultures of denitrifying bacteria or soil matrices yet (Yuan et al .…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 Through a powerful respiratory strategy, these endogenous electron mediators allow bacteria to use extracellular substrates that cannot be physically contacted (e.g., solid-phase electron acceptors with hydrophilic interfaces). 19 , 20 …”
Section: Introductionmentioning
confidence: 99%